THE EDUCATIONAL VALUE OF THE MUNGGAH MOLO TRADITION IN SUMUB LOR VILLAGE, SRAGI DISTRICT, PEKALONGAN DISTRICT - Salsabila; Sri Prastiti Kusuma Anggraeni (Esteem Journal of English Education Study Programme, 2023)
The aim of this research is to describe the form of the munggah molo tradition and the educational values ​​in the munggah molo tradition in Sumub Lor Hamlet, Sragi District, Pekalongan Regency. This research uses a qualitative descriptive method using observation, interview and documentation techniques. The approach used is a folklore approach. The results of this research are that the munggah molo tradition is a tradition that is partly oral, because the munggah molo tradition is a hereditary activity of the people in Sumub Lor Hamlet which is still carried out every time they build a house. The form of the munggah molo tradition is a series of processions, traditions and rituals contained in the munggah molo tradition. The processions include pitung, sitting batur, munggah molo, walimahan. The educational values ​​contained in the munggah molo tradition include, among others, the value of mutual cooperation in the batur sitting procession, the value of caring in the walimahan procession, religious values ​​in the munggah molo procession.